2018
DOI: 10.3390/ma11030355
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Charge Extraction of Li-Doped TiO2 for Efficient Thermal-Evaporated Sb2S3 Thin Film Solar Cells

Abstract: We provided a new method to improve the efficiency of Sb2S3 thin film solar cells. The TiO2 electron transport layers were doped by lithium to improve their charge extraction properties for the thermal-evaporated Sb2S3 solar cells. The Mott-Schottky curves suggested a change of energy band and faster charge transport in the Li-doped TiO2 films. Compared with the undoped TiO2, Li-doped mesoporous TiO2 dramatically improved the photo-voltaic performance of the thermal-evaporated Sb2S3 thin film solar cells, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The higher FF of the SOL-5.8-MP compared to that of the SOL-5.8-CL devices, resulting in higher PCE, is attributed to the added Li-doped mesoporous-TiO 2 layer, which facilitates efficient electron extraction at the perovskite-TiO 2 interface and passivates trapping states in TiO 2 . 47,48 Moreover, the presence of the MP-TiO 2 layer reduces the possible direct contact between the perovskite layer and the FTO electrode, which could occur due to the possible presence of tiny voids in the CL-TiO 2 layer (see Fig. S7(a)-(c) for the morphology of the TiO 2 films).…”
Section: Resultsmentioning
confidence: 99%
“…The higher FF of the SOL-5.8-MP compared to that of the SOL-5.8-CL devices, resulting in higher PCE, is attributed to the added Li-doped mesoporous-TiO 2 layer, which facilitates efficient electron extraction at the perovskite-TiO 2 interface and passivates trapping states in TiO 2 . 47,48 Moreover, the presence of the MP-TiO 2 layer reduces the possible direct contact between the perovskite layer and the FTO electrode, which could occur due to the possible presence of tiny voids in the CL-TiO 2 layer (see Fig. S7(a)-(c) for the morphology of the TiO 2 films).…”
Section: Resultsmentioning
confidence: 99%
“…The slight concentration of Sb atom at the interface of Sb 2 (S,Se) 3 /CdS, which may be caused by the a high MCN and low selenization temperature, may lead to rich sulfur vacancies. It has demonstrated that more sulfur vacancies in the absorber is able to increase the concentration of electrons and improve the V oc of the device . But the severe recombination resulted by the defects also cannot be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…Although the remarkable grain size of the thin film can greatly reduce the numbers of grain boundaries from surface to depletion region, which will alleviate the recombination loss during charge carrier transportation. [53] But the severe recombination resulted by the defects also cannot be ignored. In addition, a 368 mV loss of present heterojunction was demonstrated when comparing with the built-in voltage of 1.1 V. It indicates that the quality of the heterojunction is not ideal.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…For this problem, by neglecting the quality of absorber, the band gap offset alignment is expected to solve this problem effectively through improving the extraction of charge carriers. It has been demonstrated that the transportation of electrons between the absorber layer and the electron transporting layer can make a great influence on the PCE of Sb 2 (S,Se) 3 thin film solar cells by tuning the band gap offset at the interface . In addition, series works basing on various electron transporting layer have been carried out by Tang's group, which revealed that the selection of a better electron transporting layer for Sb 2 (S,Se) 3 thin film solar cells is very important.…”
Section: Introductionmentioning
confidence: 99%